Relations of Safavi Sheikhs With Ottoman Sultans - Rahimli, Gunel (Scholarya Demo Journal of Ruby, 2019)
The Safaviyya sect founded by Sheikh Safiuddin Ishaq in Ardebil in 1300 hasexpanded its scope with great popularity among the people in a short time. BeyondAzerbaijan there was also a mass of supporters in Turkistan, Syria and Anatolia.Eastern Anatolia was taking special place with its crowd of followers. The majorityof the followers of the Safaviyya sect living in Anatolia were semi-nomadic turkmanclans. If we consider that at that time Anatolia was under the control of the Ottomanstate, then we can say that the Ottoman-Safavid relations was necessary, from theinitial times of the Safaviyya sect. This necessitated the establishment of theOttoman-Safavid relations from the earliest days of the Safaviyya sect. Initially, theOttoman sultans were followers of this sect and were providing them good help. Butduring the leadership of Sheikh Juneyd (1447-1460), when the political ambitions ofthe Safaviyya sect appeared, the attitudes of the Ottoman sultans to the sect changed. The Safaviyya sect directly threatened Ottoman statehood when they decided tocreate a state. Because the supporters living in the lands of the Ottoman state weredeeply mentally connected with the ideology of the Safavids and were supportingthem in this struggle. From the Ardabil sect, special caliphs were sent to Anatolia tostrengthen the image of the sect to by their local agitations. Most turkman familieswhich were loyal to Safavids left the territory of the Ottoman state and moved toArdabil. The Ottoman state was not able to resist this resettlement and such caseswere the causes of deterioration of Ottoman-Safavids relations. In this article, the relations between the Ottoman sultans and Safavi sheiksduring the Safaviyya sect were investigated.